2020
DOI: 10.1002/jmv.25971
|View full text |Cite
|
Sign up to set email alerts
|

Pooling of nasopharyngeal swab specimens for SARS‐CoV‐2 detection by RT‐PCR

Abstract: Until an effective vaccine is available, interruption of community circulation of SARS-CoV-2 is crucial to control virus spread. To this end, systematic testing of large population groups by RT-PCR is mandatory to case identification and contact tracing thereby minimizing the likelihood of resurgence in contagion. 1 This approach faces a variety of obstacles, most notably the limited availability of reagents resources. Sample pooling for RT-PCR has been effectively used for screening of blood donors for Human … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
90
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 9 publications
16
90
0
1
Order By: Relevance
“…As previous studies [8,9,18], our results using pools showed an increase of 3-5 cycles in the Cq value between pooled tests and individual positive samples. It has not carried out loss of sensitivity in pools for samples with Cq value within the rst three quartiles observed in our population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As previous studies [8,9,18], our results using pools showed an increase of 3-5 cycles in the Cq value between pooled tests and individual positive samples. It has not carried out loss of sensitivity in pools for samples with Cq value within the rst three quartiles observed in our population.…”
Section: Discussionsupporting
confidence: 89%
“…Pooling strategies have proven to preserve SARS-CoV-2 testing resources and time with an increase in testing capability of the 69% for an incidence rate of SARS-CoV-2 infection of 10% or less [4,5,6,7], but it could be associated with a decrease in detection [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The pooling method was validated for nCov tests by many laboratories [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, the following questions remained open, which we address in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome some of these limitations, laboratories have adapted and developed innovative methods for testing, such as the pooling of two or more samples either prior to, or after, nucleic acid extraction, [32][33][34][35] which has been done previously for the mass screening of samples for influenza virus. 36 If SARS-CoV-2 RNA is subsequently detected, repeat testing of the individual samples from the original pool is performed 37 However, the advantages of pooling are negated when the prevalence of COVID-19 in the population tested is high, as more pooled samples will require individual testing.…”
Section: Sars-cov-2 Nucleic Acid Testingmentioning
confidence: 99%